2016
DOI: 10.7717/peerj.2699
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the complete chloroplast genome sequences in psammophyticHaloxylonspecies (Amaranthaceae)

Abstract: The Haloxylon genus belongs to the Amaranthaceae (formerly Chenopodiaceae) family. The small trees or shrubs in this genus are referred to as the King of psammophytic plants, and perform important functions in environmental protection, including wind control and sand fixation in deserts. To better understand these beneficial plants, we sequenced the chloroplast (cp) genomes of Haloxylon ammodendron (HA) and Haloxylon persicum (HP) and conducted comparative genomic analyses on these and two other representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 42 publications
5
49
3
Order By: Relevance
“…Fifty-four SSRs (19.64%) were located in intron regions. The distribution of SSRs is variable significantly among the four regions in each of the six Lagerstroemia cp genomes, which is identical with previous reports (Dong et al, 2016; Yang et al, 2016). …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Fifty-four SSRs (19.64%) were located in intron regions. The distribution of SSRs is variable significantly among the four regions in each of the six Lagerstroemia cp genomes, which is identical with previous reports (Dong et al, 2016; Yang et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…Although cp genomes are highly conserved in terms of genomic structure and size, the IR/SC junction position change caused by expansion and contraction of the IR/SC boundary regions was usually considered as a primary mechanism in creating the length variation of the higher plant cp genomes (Kim and Lee, 2005; Asaf et al, 2016; Dong et al, 2016; Yang et al, 2016; Zhang et al, 2016). In this study, however, the IR/SC junction position change was not observed among the six cp genomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations